The influence of the Ionic Liquid [C14MIM][Cl] on the structural and thermodynamic features of zwitterionic and anionic model membrane - Oliveira, Luma Melo de (2017)
Ionic Liquids (ILs) has been attracting attention, both from academia and industry, given the numerous applications of these systems. ILs are salts, usually composed by an organic ion, and a counterion which could be organic or inorganic, and, interestingly they are found at liquid state at room temperature. Our interest in studying ILs comes from its low toxicity. Some recent studies have shown that the toxicity of the ILs ishigher than believed, in particular for biologically relevant systems. The main goal of this research is to study the influence of the ionic liquid 1-tetradecyl-3-methylimidazolium chloride ([C14MIM][Cl]) with membrane systems. To do so, we made use of different lipids: POPC, Sphingomyelin, Cholesterol, POPG, DPPC, DPPG and DMPC. For each of these systems, the influence of ILs concentration were elucidated by means of a systematic study through different experimental techniques: Small Angle X-ray scattering (SAXS), dynamic light scattering (DLS), fluorescence anisotropy, optical microscopy and z-potential. Since [C14MIM][Cl] has a positive charge on the imidazolium group, the superficial charge of all vesicles increased. For zwitterionic vesicles no significant change in size and melting temperature were noticed. The imidazolium-based ionic liquid diminished the gel-fluid transition temperature for negatively charged lipids. For DPPC:DPPG (1:1), for instance, the transition temperature decreased from 42.50±0.13oC to 25.27±0.33oC and for DPPG from 46.12±0.22 oC to 36.6±0.38 oC. For DPPG, the vesicle hydrodynamic diameter increased from 84±0.1nm to 176±0.1nm, whereas for DPPC:DPPG it increased from 95±0.1nm to 196±0.1nm. The electronic density profile, obtained by SAXS, supported the penetration of the [C14MIM][Cl] into the negative bilayer structure. 15 mol% of [C14MIM][Cl] increased the polar head thickness of DPPC vesicles from 11.1±0.6 Å to 18.0±0.7 Å, without alter significantly the inner region of the membrane.Qualitative results obtained with optical microscopy showed that the IL incorporation destabilize the membrane asymmetry (between the leaflets) leading to the formation of pores (evidenced by optical contrast lost) and the presence of buds. We believe that this work could improve the understanding of the effects of ILs in the presence of biological relevant systems